SMAD7 regulates proinflammatory and prolabor mediators in amnion and myometrium†. Issue 2 (26th July 2017) - Lim, Ratana; Barker, Gillian; Lappas, Martha
Abstract: Preterm birth continues to be a significant public health problem. Infection (bacterial and or viral) and inflammation, by stimulating proinflammatory cytokines, adhesion molecules, and matrix metalloproteinase 9 (MMP9), play a central role in the rupture of membranes and myometrial contractions. SMAD7 has been implicated in regulating the inflammatory response; however, no studies have been performed with regard to human labor. In this study, we determined the effect of spontaneous human labor and prolabor mediators on SMAD7 expression in myometrium and fetal membranes. Functional studies were employed to investigate the effect of siRNA knockdown of SMAD7 (siSMAD7) in regulating infection and inflammation-induced prolabor mediators. SMAD7 mRNA and protein expression were significantly higher with spontaneous term labor, compared to no labor, in myometrium and fetal membranes. SMAD7 expression was also significantly higher in amnion from women with preterm chorioamnionitis. The proinflammatory cytokines IL1B and TNF, the bacterial product fsl-1, and the viral dsRNA analog poly(I:C) significantly increased SMAD7 in myometrial cells and amnion cells. In myometrial cells, siSMAD7 cells significantly decreased cytokine (IL6) and chemokine (CXCL1, CXCL8, CCL2 are also known as GRO-alpha, interleukin (IL)-8 and monocyte chemotactic protein-1 (MCP-1)) production induced by IL1B, TNF, and fsl-1. There was also a decrease in the expression of adhesion molecules intercellular adhesion molecule 1 (ICAM1) and vascular cell adhesion molecule 1 (VCAM1) in siSMAD7 cells, and MMP9 expression. In amnion, siSMAD7 cells treated with IL1B also decreased cytokine and chemokine production, ICAM1 and MMP9 expression. In conclusion, we report a proinflammatory role for SMAD7 in human gestational tissues, with SMAD7 silencing attenuating the inflammatory response. Summary Sentence: SMAD7 expression is increased in laboring myometrium and by mediators of labor; SMAD7 is involved in the regulation of prolabor mediators induced by inflammation.